Evaluation of the mental skills of Japanese elite athletes - Murakami, K.; Hiraki, T.; Uto, M.; Arai, H.; Tachiya, Y. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Psychological variables are very important for success in sports. Indeed for the same physical, technique and tactics characteristics, some athletes achieve excellent performance, while also fail to emerge. In Japan Institute of Sports Sciences (JISS), as a part of the medical and fitness checkup prior to the Olympic Games, mental skills of the athletes were assessed. One key factor in bringing an athlete`s capability into full play is mental skills. Therefore, the purpose of this work is to study the mental skills of Olympians and compare them with those of less successful players. Methods: In collaboration with the JISS, we recruited a sample of 1965 elite athletes, divided into Olympians (n=915) and national level (n=1050). Olympians representing 49 different Olympic sports served as participants. The instrument used was the Diagnostic Inventory of Psychological Competitive Ability for athletes (DIPCA.3, Tokunaga, 2001). The questionnaire inludes 52 items and 12 mental skills scales grouped under 5 broader conceptual components. To evaluate the differences between the two sub-samples we conducted a multivariate analysis of variance (MANOVA) using level of competition and gender as independent variables, and the average scores of scale as dependent variables. Results: Results of analysis revealed several differences between psychological characteristics of athletes as function of their performance level. Significant differences appeared in almost scales Means comparisons revealed that Olympians exhibited superior mental skills than national players in patience, aggressiveness, volition for selfrealization, self-control, ability to relax, concentration, confidence, decisiveness, predictive ability, and judgment. By contrast, Olympians scord slightly lower in volition for winning and cooperation. Discussion: This study has shown that there are significant differences in mental abilities depending on the level of competition. Olympians were better than national athletes in patience, aggressiveness, volition for self-realization, self-control, ability to relax, concentration, confidence, decisiveness, predictive ability, and judgment. Findings corroborate the results of previous studies (Gould et al., 2002) comparing mental skills of elite and non-elite athletes. The knowledge of the features of elite athletes may be useful to provide mental training programs relevant to successful performance.